Gut bacterial microbiota in patients with myasthenia gravis: results from the MYBIOM study. (August 2021) - Totzeck, Andreas; Ramakrishnan, Elakiya; Schlag, Melina; Stolte, Benjamin; Kizina, Kathrin; Bolz, Saskia; Thimm, Andreas; Stettner, Mark; Marchesi, Julian R.; Buer, Jan; Kleinschnitz, Christoph; Verhasselt, Hedda Luise; et al.
Background: Myasthenia gravis (MG) is an autoimmune neuromuscular disease, with gut microbiota considered to be a pathogenetic factor. Previous pilot studies have found differences in the gut microbiota of patients with MG and healthy individuals. To determine whether gut microbiota has a pathogenetic role in MG, we compared the gut microbiota of patients with MG with that of patients with non-inflammatory and inflammatory neurological disorders of the peripheral nervous system (primary endpoint) and healthy volunteers (secondary endpoint). Methods: Faecal samples were collected from patients with MG ( n = 41), non-inflammatory neurological disorder (NIND, n = 18), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP, n = 6) and healthy volunteers ( n = 12). DNA was isolated from these samples, and the variable regions of the 16S rRNA gene were sequenced and statistically analysed. Results: No differences were found in alpha- and beta-diversity indices computed between the MG, NIND and CIDP groups, indicating an unaltered bacterial diversity and structure of the microbial community. However, the alpha-diversity indices, namely Shannon, Chao 1 and abundance-based coverage estimators, were significantly reduced between the MG group and healthy volunteers. Deltaproteobacteria and Faecalibacterium were abundant within the faecal microbiota of patients with MG compared with controls with non-inflammatory diseases. Conclusion: Although the overall diversity and structure of the gut microbiota did not differ between the MG, NIND and CIDP groups, the significant difference in the abundance of Deltaproteobacteria and Faecalibacterium supports the possible role of gut microbiota as a contributor to pathogenesis of MG. Further studies are needed to confirm these findings and to develop possible treatment strategies.